Math, asked by SinghSaab7154, 1 year ago

If A=B=60°, verify that
(i)cos(A-B)=cosAcosB+sinAsinB
(ii)sin(A-B)=sinAcosB-cosAsinB
(iii)tan(A-B)=tanA-tanB/1+tanatanB

Answers

Answered by harendrachoubay
3

i) \cos(A-B)=\cos A \cos B+\sin A\sin B, verified.

ii) \sin(A-B)=\sin A \cos B-\cos A\sin B, verified.

iii) \tan(A-B)=\dfrac{\tan A-\tan B}{1+\tan A\tan B}, verified.

Step-by-step explanation:

We have,

A = B = 60°

To verify:

i) \cos(A-B)=\cos A \cos B+\sin A\sin B

ii) \sin(A-B)=\sin A \cos B-\cos A\sin B

iii) \tan(A-B)=\dfrac{\tan A-\tan B}{1+\tan A\tan B}

i) L.H.S. = \cos(A-B)

= \cos(60-60)

= \cos 0

= 1

R.H.S. = \cos A \cos B+\sin B\sin B

= \cos 60 \cos 60+\sin 60\sin 60

= \dfrac{1}{2}.\dfrac{1}{2} +\dfrac{\sqrt{3}}{2}. \dfrac{\sqrt{3}}{2}

= \dfrac{1}{4}+\dfrac{3}{4}

= \dfrac{1+3}{4}

= 1

L.H.S. = R.H.S. = 1, verified.

ii) L.H.S. = \sin(A-B)

Put A = B = 60°, we get

= \sin(60-60)

= \sin 0

= 0

R.H.S. = \sin A \cos B-\cos A\sin B

Put A = B = 60°, we get

= \sin 60 \cos 60-\cos 60\sin 60

= \dfrac{\sqrt{3}}{2} \dfrac{1}{2} -\dfrac{1}{2}\dfrac{\sqrt{3}}{2}

= 0

L.H.S. = R.H.S. = 0, verified.

iii) L.H.S. = \tan(A-B)

Put A = B = 60°, we get

= \tan(60-60)

= \tan 0

= 0

R.H.S. = \dfrac{\tan A-\tan B}{1+\tan A\tan B}

= \dfrac{\tan 60-\tan 60}{1+\tan 60\tan 60}

= \dfrac{\sqrt{3}-\sqrt{3}}{1+\sqrt{3}\sqrt{3}}

= \dfrac{0}{1+3}

= 0

L.H.S. = R.H.S. = 0, verified.

Answered by BrainlyPARCHO
0

\large { \fcolorbox{gray}{black}{ ✔\: \textbf{Verified \: answer}}}

i)

 \bf \: L.H.S.  \\ = \cos(A-B) \\ = \cos(60-60) \\ = \cos 0 \\ = 1 \\  \\  \bf \: R.H.S.  \\ = \cos A \cos B+\sin B\sin B \\ = \cos 60 \cos 60+\sin 60\sin 60 \\ = \dfrac{1}{2}.\dfrac{1}{2} +\dfrac{\sqrt{3}}{2}. \dfrac{\sqrt{3}}{2}  \\ = \dfrac{1}{4}+\dfrac{3}{4}  \\ = \dfrac{1+3}{4}  \\ = 1

▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬

ii)

 \bf \: L.H.S.  \\ = \sin(A-B)sin(A−B) \\ Put A = B = 60°, we get \\ = \sin(60-60) \\ = \sin 0 \\ = 0 \\  \\  \bf \: R.H.S.  \\ = \sin A \cos B-\cos A\sin B \\ Put A = B = 60°, we get \\ = \sin 60 \cos 60-\cos 60\sin 60 \\ = \dfrac{\sqrt{3}}{2} \dfrac{1}{2} -\dfrac{1}{2}\dfrac{\sqrt{3}}{2}  \\ = 0

▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬▬

iii)

 \bf \: L.H.S.  \\ = \tan(A-B)tan(A−B) \\ Put A = B = 60°, we get \\ = \tan(60-60) \\ = \tan 0 \\ = 0 \\  \\  \bf \: R.H.S. \\  \dfrac{\tan A-\tan B}{1+\tan A\tan B}  \\  \dfrac{\tan 60-\tan 60}{1+\tan 60\tan 60}  \\ \dfrac{\sqrt{3}-\sqrt{3}}{1+\sqrt{3}\sqrt{3}}  \\  \dfrac{0}{1+3}

Similar questions